Why do firms oppose entry-deterring policies? Environmental regulation and entry deterrence. (23rd April 2014) - Espínola-Arredondo, Ana; Muñoz-García, Félix
Abstract: This paper investigates the design of environmental regulation under different regimes: flexible and inflexible policies. We analyze under which settings strict emission fees can be used as an entry-deterring tool, and become socially optimal. Furthermore, we demonstrate that the incentives of the social planner and the incumbent firm are aligned regarding policy regimes ifentry can be easily deterred by setting a stringent regulation. Their incentives, however, can bemisaligned when entry becomes more costly to deter, leading the incumbent to actually preferenvironmental policies that attract entry.